Screening for Natural Producers Capable of Producing 1,3-Propanediol from Glycerol - Andriani, Dian; Kusharyoto, Wien; Prasetya, Bambang; Wilke, Thomas; Vorlop, Klaus Dieter (ANNALES BOGORIENSES, 2010)
Glycerol is a renewable resource found as the mainÂ  by-product in the transesterification of triglycerides and fat saponification. Due to the increased production of plant oils, especially palmÂ  oilÂ  in developing countries, and their larger useÂ  by the oleochemical industry, glycerol surpluses are on the world market and this may result in a desrease in glycerolÂ  price. As a consequence, biotechnological processesÂ  have been developed to convert this substrateÂ  intoÂ  value-addedÂ  products,Â  suchÂ  asÂ  1,3-propanediolÂ  (1,3-PD).Â  TheÂ  microbialÂ  productionÂ  ofÂ  1,3-PD couldÂ  beÂ  competitiveÂ  toÂ  chemicalÂ  routesÂ  assumingÂ  thatÂ  itÂ  isÂ  basedÂ  onÂ  cheapÂ  rawÂ  materialÂ  andÂ  anÂ  optimized process.Â  InÂ  theÂ  screeningÂ  forÂ  1,3Â  PDâproducingÂ  bacteria,Â  rawÂ  glycerolÂ  asÂ  by-productÂ  fromÂ  rapeseedÂ  oil processing unitÂ  wasÂ  usedÂ  asÂ  aÂ  carbonÂ  sourceÂ  comparedÂ  withÂ  commercialÂ  glycerol.Â  ByÂ  usingÂ  increasing concentration ofÂ  bothÂ  glycerolsÂ  fromÂ  50Â  toÂ  150Â  g/l,Â  twoÂ  potentialÂ  bacteriaÂ  wereÂ  obtainedÂ  fromÂ  soilÂ  samples.BMP 1 was obtained from an enrichment culture using 50 g/l commercial glycerol, while BMR-1 was obtained from Â an enrichment culture using 100 g/l raw glycerol. The highest conversion yield obtained using the isolateBMP-1 was around 0.62 g 1,3-PD formed perÂ  mol glycerol consumed, and 0.73Â  mol 1,3-PDÂ  formed perÂ  molgycerol using the isolate BMR-1. No bacteria were obtained from cultures using 150 g/l commercial and rawgycerol, respectively, which indicated that higher concentration of glycerol has inhibition effect. Â  Keywords: 1,3-propanediol, enrichment culture, glycerol, palm oil, screening